PERANAN BRAND IMAGE DAN BRAND CREDIBILITY DALAM MENINGKATKAN LOYALTY INTENTION MELALUI BRAND COMMITMENT - Keni Keni; Callista Callista (Universitas Mercu Buana, 2021)
The purpose of this research is to examine whether 1) brand image can predict loyalty intention 2) brand credibility can predict loyalty intention 3) brand credibility can predict brand commitment 4) brand commitment can predict loyalty intention 5) brand commitment mediates the effect of brand credibility on loyalty intention. Sample was selected using convenience sampling method amounted to 173 respondents. Data processing techniques using structural equation modeling what helped by Smart PLS 3.2.7 program. The result of this study shows that brand credibility, and brand commitment have significant effect to predict loyalty intention, but brand image doesn’t, brand credibility has significant effect to predict brand commitment, and brand commitment mediates the effect of brand credibility on loyalty intention.